Protection of historic public spaces in the creative process of the city's identity. - Zbigniew Władysław Paszkowski; Sylwia Kołowiecka; Aleksandra Kuśmierek (Ochrona Dziedzictwa Kulturowego)
This article addresses the development of new identity in cities returned to Poland after the Second World War, taking the example of Szczecin (fig. 1). This process is characterized by many years of changes: reconstruction, revalorization and revitalization of urban complexes. In the process of creating a new, Polish identity of those cities, focus was clearly placed on the functionalist development of urban structures and strongly emphasized comprehensive functionality of downtown spaces. This trend seriously threatened historic public spaces preserved in these areas. However, it is also necessary to take into account the growing requirements regarding functionality and quality of life as well as needs related to the contemporary utility of historic urban areas. A living, developing city cannot be insulated from changes resulting from economic, technological and cultural development, or from the utilitarian needs of its inhabitants. Urban revitalization is a method that thoughtfully protects the historical value of buildings, while allowing new functions and activities, appropriately selected in terms of heritage protection. In these processes, special attention should be paid to historic public spaces where urban life takes place as they are crucial for the city’s identity. Negotiating the city’s social identity takes place mainly in historical public spaces, where the reliability of the approach to the protection of historical values and resources is the condition for social acceptance.